The Effect of Corporate Governance Quality, Firm Size, Leverage, and Financial Performance on Intellectual Capital DisclosureEmpirical Study: Manufacturing Companies Listed on the IDX - Luthan, Elvira; Ayu, Sandra; ., Ilmainir (International Journal of Engineering and Technology, 2018)
Purpose - This study aims to determine the effect of corporate governance quality, firm size, leverage, and financial performance on intellectual capital disclosure (ICD), in manufacturing companies listed on Indonesian Stock Exchange. Methodology - The observation period is from 2010 to 2015. The sample is chosen by purposive random sampling method so that 45 companies as sample are obtained. This study used a secondary data and multiple linear regression analysis method. Data tabulation was processed using SPSS version 19.0 for Windows. Findings - The corporate governance quality, firm size, and financial performance in which measured to ROA and EPS showed to have positive significant effect on the ICD. This is shown from the significant value smaller than Î± of 0.05 and positive t value. Meanwhile, leverage has negative significant effect on the ICD with the result showed that leverage variable has the significant value smaller than Î± of 0.05 and negative t value. Contribution - This study supports agency theory and signaling theory. The results of the research can be input for the accounting standards making body that the disclosure of intellectual capital in the financial statements is necessary because it can improve the performance of the company.Â